Sintering parameter optimization with quality engineering technique : best flexure strength - Jamaludin, Khairur Rijal (2009)
Metal injection moulding (MIM) is a net-shape process which combines the versatility of plastic injection moulding with the strength and integrity of machined, pressed or otherwise manufactured small, complex, metal parts. The process combines the design freedom of plastic injection moulding with material properties near that of wrought metals. Optimisation of the processing parameter is essential to obtain high quality final parts. Rigid final part is essential to maintain an excellent performance of the powder metallurgy products especially for the tough application such as automotive, defence and industrial tools. Many earlier studies about sintering of MIM part are concerning with microstructures, densification, and sintering atmosphere (Li et al. 2003 [2]; Fu et al. 2005 [3]; Koseski et al. 2005 [4]; Suri et al. 2005 [5]; Berginc et al. 2006 [6]). Sintering parameters were optimised by adjusting the sintering variables without using any design of experiment (DOE) methodology.